2023
DOI: 10.1021/acssynbio.3c00259
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Base Editing System for Marine Roseobacter Clade Bacteria

Abstract: The Roseobacter clade bacteria are of great significance in marine ecology and biogeochemical cycles, and they are potential microbial chassis for marine synthetic biology due to their versatile metabolic capabilities. Here, we adapted a CRISPR-Cas-based system, base editing, with the combination of nuclease-deactivated Cas9 and deaminase for Roseobacter clade bacteria. Taking the model roseobacter Roseovarius nubinhibens as an example, we achieved precise and efficient genome editing at single-nucleotide reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Four edited strains have been selected, each with three biological independent colonies, including glnA edited by dCas9-AID, by dSpRY-AID, argH edited by dSpRY-AID, and tryB and aspC edited by dSpRY-AID (Figure 5). According to the WGS data, we found unexpected high frequency of off-target events comparing to previous reports using AID from P. marinus (Banno et al, 2018;Wang et al, 2023;Wei et al, 2023). All off-target editing were C-to-T or G-to-A transitions probably due to deamination, agreeing with previous reports (Rodrigues et al, 2021;Tong et al, 2019).…”
Section: Trade-offs Between Universality and Precisionsupporting
confidence: 90%
See 2 more Smart Citations
“…Four edited strains have been selected, each with three biological independent colonies, including glnA edited by dCas9-AID, by dSpRY-AID, argH edited by dSpRY-AID, and tryB and aspC edited by dSpRY-AID (Figure 5). According to the WGS data, we found unexpected high frequency of off-target events comparing to previous reports using AID from P. marinus (Banno et al, 2018;Wang et al, 2023;Wei et al, 2023). All off-target editing were C-to-T or G-to-A transitions probably due to deamination, agreeing with previous reports (Rodrigues et al, 2021;Tong et al, 2019).…”
Section: Trade-offs Between Universality and Precisionsupporting
confidence: 90%
“…We observed that when the loci of the target moved to positions -19 and -20, the editing efficiencies significantly increased reaching 100% and 95.45 ± 9.09%, indicating the capacity of dSpRY-AID for improving editing performance (Figure 1C). To be noticed, we also found mixed signals in the resulting colonies at the first round of selection, which is a common issue for base editing (Wei et al, 2023;Xia et al, 2020), while strains with pure edits could be obtained via one more round of segregation (Figure S2).…”
Section: Design Of a Pam-independent Base Editor For Bacteriamentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, V. natriegens developed a novel NT-CRISPR approach by expressing anti-Cas9 proteins to overcome Cas9-induced cell toxicity, generating up to 100% editing (deletion) efficiency [ 135 ]. Recently, advancement was reported in the utilization of CRISPR/dCas9 for precise and efficient single-nucleotide resolution genome editing in the aromatic compound-metabolizing bacterium Roseovarius nubinhibens [ 136 ]. This was achieved without inducing double-strand breaks or the provision of donor DNA.…”
Section: Applications On Marine Prokaryotic Microbesmentioning
confidence: 99%
“…This was achieved without inducing double-strand breaks or the provision of donor DNA. Leveraging the editing system, critical genes within the β-ketoadipate pathway unequivocally establish the indispensability of pobA , pcaH , and pcaG in the β-ketoadipate pathway for the degradation of aromatic compounds [ 136 ]. Moreover, this study revealed that the absence of pcaQ in the genome hinders the consumption of aromatic compounds.…”
Section: Applications On Marine Prokaryotic Microbesmentioning
confidence: 99%